PERBANDINGAN MAHKAMAH KONSTITUSI INDONESIA DAN VERFASSUNGSGERICHTSHOF AUSTRIA: Comparasion of IThe Indonesian Constitutional Court and Verfassungsgerichtshof Austria - Dimas Adiansyah; Dimas Adiyansyah; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2024)
The state of law needs a good constitution. one of the constitutions that can be used as a comparison is Austria. Formulation of the problem What is the position of the constitutional courts in Indonesia and Austria in the constitutional structure? And what is the membership and authority of the constitutional courts in Indonesia and Austria? The research method is based on normative law with descriptive nature. The result and conclusion, the status of the Constitutional Courts of Indonesia and Austria is both independent judicial institutions that uphold the constitution and the constitutional rights of citizens. Judges of the Indonesian Constitutional Court are prohibited from concurrently holding positions as: officials of other countries or civil servants. Meanwhile, the requirements for Austrian Constitutional Court judges are to have a degree in law or political science and at least 10 years of legal professional experience, and to be appointed by the Federal President based on decision submitted by three people. institutions, namely the Federal Government, the National Assembly and the Federal Council. The Indonesian Constitutional Court has the authority to test the constitutionality of laws. In contrast to Austrian Constitutional Court which has the authority to test constitutionality of all legal products.